Assessing the Validity and Reliability of a Questionnaire for Evaluating Pharmaceutical Services at a Hospital - Utami Putri Siregar, Giel; Rizka Amanda, Laura; Dirsam, Winarlin; Sari Dewi, Ratna (SAFE-Network, 2024)
Pharmaceutical services are vital components of the healthcare system that aim to ensure the appropriate, safe, and effective use of medicines. This study aims to develop and test the validity and reliability of a questionnaire for assessing the quality of pharmaceutical services at a hospital in Jakarta. The questionnaire was designed based on five service quality dimensions: tangibles, reliability, assurance, empathy, and responsiveness. An initial set of 23 statement items was tested for content validity by calculating the Content Validity Ratio (CVR) and Content Validity Index (CVI). Several items were eliminated for not meeting the validity threshold. Subsequently, construct validity was tested by calculating Pearson product-moment correlations on data from 100 respondents who met the inclusion criteria, resulting in 13 valid statement items with r > 0.148. Reliability tests indicated Cronbach’s Alpha values above 0.6 for all dimensions, demonstrating good internal consistency of the questionnaire. Hypothesis testing results showed that all statement items had a significant relationship with the total questionnaire score (p < 0.05). Therefore, the questionnaire is valid and reliable for evaluating the quality of pharmaceutical services at a hospital in Jakarta.